Characteristics of Soaked and Dried Water Yam Flour as Material for Producing Edible Paper - Indrastuti, Erning; harijono, Harijono; Susilo, Bambang (Jurnal Teknologi Pertanian, 2012)
This  research aimed to study the physicochemical characteristics of  water yam flour are due to soaking and drying treatments, as material for edible paper, as a substitute for rice flour in the producing of rice paper (fresh spring roll wrapper).  This study used Randomized  Block Design with two factors: soaking time of 0, 24, and 48 hours; and drying temperature at 40, 50, and 60 °C. The result showed increasing soaking decreased  mucilages, meanwhile increasing soaking time increased swelling power. Moisture content did not differ significantly (p>0.05).  Soaking 24 hours produced the highest final viscosity at all drying temperature. Soaking 24-hour and drying temperature 50 °C treatment could be suggested for producing yam flour and was recommended as  raw material for edible paper processing.Keywords: water yam flour, viscocity, swelling power, physichochemical properties, edible paper